"Design of Experiments" as a Method to Optimize Dynamic Disulfide Assemblies: Cages and Functionalizable Macrocycles. (6th December 2019) - Shear, Trevor A.; Lin, Fuding; Zakharov, Lev N.; Johnson, Darren W.
Abstract: Cyclophanes are a venerable class of macrocyclic and cage compounds that often contain unusual conformations, high strain, and unusual properties. However, synthesis of complex, functional derivatives remains difficult due to low functional group tolerance, high dilution, extreme reaction conditions, and sometimes low yields using traditional stepwise synthetic methods. "Design of experiments" (DOE) is a method employed for the optimization of reaction conditions, and we showcase this approach to generate a dramatic increase in the yield of specific targets from two different self‐assembling systems. These examples demonstrate that DOE provides an additional tool in tuning self‐assembling, dynamic covalent systems. Abstract : Acht neue Makrocylen mit reaktiven funktionellen Gruppen wurden durch Metalloid‐unterstützte Selbstorganisation synthetisiert. „Design of Experiments" wurde genutzt, um die Reaktionsbedingungen für multiple Systeme zu optimieren und die Ausbeute eines jeweils spezifischen Makrocyclus signifikant zu steigern.